2005
DOI: 10.1111/j.1365-313x.2005.02419.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of proline hydroxylation and hydroxyproline arabinogalactosylation motifs in secretory proteins

Abstract: SummaryMany secretory and several vacuolar proteins in higher plants contain hydroxylated proline residues. In many cases, hydroxyprolines in proteins are glycosylated with either arabinogalactan or oligoarabinose. We have previously shown that a sporamin precursor is O-glycosylated at the hydroxylated proline 36 residue with an arabinogalactan-type glycan when this protein is expressed in tobacco BY-2 cells (Matsuoka et al., 1995). Taking advantage of the fact that this is the only site of proline hydroxylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 31 publications
1
64
0
1
Order By: Relevance
“…Hereafter, we refer to HRGP glycosylation motifs as glycomotifs and use SP, not SO (except where protein sequencing has been performed), since we are working with proteins predicted from genomes/transcriptomes. Thus, the hydroxylation (and, therefore, glycosylation) status of Pro is unknown and context dependent (Tan et al, 2003;Shimizu et al, 2005;Kurotani and Sakurai, 2015). The relatively low sequence similarity of members is clearly evident when viewing a percentage identity matrix, where GPI-AGPs range from 9.6% to 61.6% and CL-EXTs range from 6.3% to 84.2% amino acid identity (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hereafter, we refer to HRGP glycosylation motifs as glycomotifs and use SP, not SO (except where protein sequencing has been performed), since we are working with proteins predicted from genomes/transcriptomes. Thus, the hydroxylation (and, therefore, glycosylation) status of Pro is unknown and context dependent (Tan et al, 2003;Shimizu et al, 2005;Kurotani and Sakurai, 2015). The relatively low sequence similarity of members is clearly evident when viewing a percentage identity matrix, where GPI-AGPs range from 9.6% to 61.6% and CL-EXTs range from 6.3% to 84.2% amino acid identity (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This will require detailed structural analysis of many members of each multigene family, from key transitions throughout the plant lineage. Even within a single species, glycosylation is tissue dependent and directed by the context of amino acids surrounding the glycomotif (Tan et al, 2003;Shimizu et al, 2005;Kurotani and Sakurai, 2015). As we gain further knowledge of the PTMs on HRGPs, these can be incorporated into the MAAB pipeline.…”
Section: Versatility Of the Maab Pipeline For Hrgpsmentioning
confidence: 99%
“…Mutation to Ala resulted in the production of kalata B1 with a Ctr containing the sequence GAOS. The hydroxylation of this protein appears unusual as it does not coincide with a known hydroxylation motif, although these are poorly characterized in plants (22).…”
Section: Discussionmentioning
confidence: 99%
“…6) This motif sequence can be found in a number of mammalian proteins, and it has been reported that immunoglobulin A1 produced in maize had plant-specific O-glycosylation in the hinge region consisting of many proline and serine residues. 7) The initial step in this plant-specific protein Oglycosylation is the conversion of proline residues to Hyp residues catalyzed by prolyl-4-hydroxylases (P4Hs).…”
mentioning
confidence: 99%
“…6,13) We first analyzed whether such a glycosylated smear could be seen in a transgenic tobacco plant which expressed sporamin under the control of the CaMV 35S promoter. 14) Twoweek-old seedlings of transgenic tobacco plants germinated on a solid MS medium were hydroponically grown for two weeks at 28 C in vitro on a 3-cm cube of rockwool placed at the center of an Agripot (Iwaki, Tokyo, Japan) and immersed in 50 mL of a quarterconcentration of a Hoagland liquid medium.…”
mentioning
confidence: 99%